A new fern species hypodematium shandongense sp. Nov. (hypodematiaceae) from china (Bangladesh Journal of Botany, 2023)
Hypodematium shandongense is closely related to Hypodematium jianxiuii X. J. Li. Results of LM and SEM studies showed that there were significant differences between the two species. Plant height of Hypodematium shandongense is 22-30 cm, laminae ovate-triangular, pinnae are closely arranged, fronds, rachis, costae and the indusia are characterized by sparsely long acicular and rod-shaped glandular hairs, perispore semi-annular folds; but the plant height of H. jianxiuii is 60-70 cm, laminae ovate-pentagonal, pinnae are sparsely arranged, fronds sparsely covered with short acicular hair adaxially, abaxial fronds, rachis, costae and the indusia are densely covered with pubescence and glandular hairs, and perispore tuberculate protrusion.Bangladesh J. Bot. 52(2): 671-677, 2023 (June) Special